A SERS Study of Charge Transfer Process in Au Nanorod–MBA@Cu2O Assemblies: Effect of Length to Diameter Ratio of Au Nanorods - Lin Guo; Zhu Mao; Sila Jin; Lin Zhu; Junqi Zhao; Bing Zhao; Young Mee Jung (Nanomaterials, 2021)
Surface-enhanced Raman scattering (SERS) is a powerful tool in charge transfer (CT) process research. By analyzing the relative intensity of the characteristic bands in the bridging molecules, one can obtain detailed information about the CT between two materials. Herein, we synthesized a series of Au nanorods (NRs) with different length-to-diameter ratios (L/Ds) and used these Au NRs to prepare a series of core–shell structures with the same Cu2O thicknesses to form Au NR–4-mercaptobenzoic acid (MBA)@Cu2O core–shell structures. Surface plasmon resonance (SPR) absorption bands were adjusted by tuning the L/Ds of Au NR cores in these assemblies. SERS spectra of the core-shell structure were obtained under 633 and 785 nm laser excitations, and on the basis of the differences in the relative band strengths of these SERS spectra detected with the as-synthesized assemblies, we calculated the CT degree of the core–shell structure. We explored whether the Cu2O conduction band and valence band position and the SPR absorption band position together affect the CT process in the core–shell structure. In this work, we found that the specific surface area of the Au NRs could influence the CT process in Au NR–MBA@Cu2O core–shell structures, which has rarely been discussed before.